2005
DOI: 10.1111/j.1442-2050.2005.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Stent insertion or endoluminal brachytherapy as palliation of patients with advanced cancer of the esophagus and gastroesophageal junction. Results of a randomized, controlled clinical trial

Abstract: Esophageal cancer often presents as advanced stage disease with a dismal prognosis, with only 10-15% of patients surviving 5 years. Therefore, in a large proportion of patients, palliative treatment is the only option available. The aim of this study was to prospectively compare the palliative effect of self-expandable stent placement with that of endoluminal brachytherapy regarding the effect on quality of life and on specific symptoms. Sixty-five patients with advanced cancer of the esophagus or gastroesopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(98 citation statements)
references
References 34 publications
4
86
0
8
Order By: Relevance
“…However, patients who were treated with endoluminal stents had a clear advantage in terms of rapidity of symptom resolution. In a Swedish trial, Bergquist et al 13 showed that dysphagia scores (dss) and quality-of-life scores were better in the stent group than in the brachytherapy group at 1 month of follow-up. However, patients who survived more than 6 weeks showed far better outcomes with brachytherapy, especially in terms of recurrence of dysphagia, which was greater in the stent group because of migration and tumor ingrowth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, patients who were treated with endoluminal stents had a clear advantage in terms of rapidity of symptom resolution. In a Swedish trial, Bergquist et al 13 showed that dysphagia scores (dss) and quality-of-life scores were better in the stent group than in the brachytherapy group at 1 month of follow-up. However, patients who survived more than 6 weeks showed far better outcomes with brachytherapy, especially in terms of recurrence of dysphagia, which was greater in the stent group because of migration and tumor ingrowth.…”
Section: Resultsmentioning
confidence: 99%
“…Although two randomized controlled trials comparing endoluminal stenting with brachytherapy have shown a certain advantage for brachytherapy in terms of long-term relief from dysphagia, those trials failed to address many important issues, including the lag time between diagnosis and treatment, the time spent in treatment, and the efficacy of combined-modality treatments with both stenting and radiotherapy 12,13 . We undertook the present study to shed light on some of those issues and to attempt to identify an ideal approach to this difficult clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique may be used alone or in combination with external beam radiotherapy with or without chemotherapy. The indication of brachytherapy is the treatment of superficial esophageal cancer for curative intent in Japan (local control rate: 79-85 %) [28][29][30][31][32][33][34]; on the other hand, it is used to relieve symptom such as dysphagia for palliative intent in the treatment of advanced esophageal cancer in Western countries [35,36]. Brachytherapy involves intraluminal placement of a radioactive source into the esophagus with an intraorally or intranasally inserted applicator.…”
Section: Brachytherapymentioning
confidence: 99%
“…Although brachytherapy was found to be preferable, there are studies (such as Refs. [27,28]) suggesting the stent placement may play an important role for the palliation of disease. In that case, the prognostic models were used as evidence-based tools in decision making.…”
Section: Brachytherapy Of Esophageal Cancermentioning
confidence: 99%